DNA Extraction of Sumatran Striped Rabbit from Tissue Samples - Saputra, Rio Firman; Setiawan, Arum; Yustian, Indra; Patriono, Enggar (BIOVALENTIA: Biological Research Journal, 2019)
The Sumatran Striped Rabbit (Nesolagus netscheri ) is a naturally rare, which is a protected animal based on Government Regulation Number 7 of 1999 and renewal of Permen LHK No. P.106 which are categorized as Data Deficient by the IUCN (International Union of Conservation of Nature) since 2019. Samples were obtained from Pagar Alam, South Sumatra. Most commonly found at elevations above 600 m in montane and sub-montane primary habitat. Molecular genetic characterization of sumatran striped rabbit is to know genetic information and genetic identification of N. netscheri. Primers 12S rRNA were used in this study to characterize Sumatran striped rabbit. A 1 band were detected ranged from 900 to 1000 bp. Molecular markers represent reliable tools which may have a great impact in rabbit breeding and genetic improvement of rabbits. Molecular markers on Nesolagus netscheri is expected to tools in the identification of Sumatran striped rabbits from South Sumatra.